Clonagem de Coffea arabica L. por enraizamento de segmentos de ramos ortotrópicos - Rezende, Tiago Teruel (2016)
Methods that allow cloning of coffee plants can be useful in breeding programs and for the commercial production of seedlings. Due to the need for information that leads to the optimization of the process for obtaining clonal seedlings of Coffea arabica L. by rooting stem segments, the objective of this work was to evaluate the employment of mini-cutting in the formation of clonal seedlings of C. arabica, quantify the association between the characters of the shoot and of the root system, as well as its relations of cause and effect, in order to obtain information that may be useful for defining the procedures that allow the obtaining of clonal seedlings with good characteristics. The mini-cuttings of the semi-apical, intermediate and semi-basal portions of the orthotropic branches provided better growth to the clonal seedlings. The results indicated a dependency of the characters of the root system with those of the shoot, for clones obtained from either cutting or mini-cutting, considering that high values of dry leaf weight, plant height and number of leaves are associated with high values of dry root weight and area and volume of the roots. Culture managing practices that avoid and provide an adequate environment for the growth of the root system must be adopted to produce coffee clonal seedlings with good characteristics.